CONSILIENCE IN THE SOCIAL SCIENCES: OPPORTUNITIES AND CONSTRAINS - Pejkovic, Kristina (Politeia, 2023)
In the 20th century, the term ’consilience’ was popularized by Edward Wilson, who believed that it was possible to reconcile three major branches of knowledge: the sciences, the social sciences, and the humanities. The consilient explanation is based on the assumption of the possibility of unification of scientific knowledge and epistemological continuity. In the sciences, the problem of epistemological continuity is far less controversial than in the social sciences, and most scientists believe that there is a continuity between physics, chemistry, and biology. There are social and epistemological reasons why that problem is most often neglected in the social sciences. Today’s popularity of postmodernism, poststructuralism, and similar relativistic orientations testifies to the lack of desire of social scientists to search for connections between sciences, and only a small number of scientists want to make an analogous connection between the fields. On the other hand, there are ideas and fears that it is not even desirable to establish this intellectual continuity because it reminds us of the reductionism that is most often criticized in the field of social sciences. And, finally, there is a significant number of authors who believe that it is not possible to achieve it due to the nature of knowledge of the social sciences. The thesis of this paper is that, at least, moderate consilience is possible in the social sciences as well. It requires the synthesis of knowledge from different scientific disciplines that explore the same problem to form coherent conclusions about the given phenomenon. This paper aims to point out the importance of cooperation between sociology and other scientific disciplines that study different levels of analysis of phenomena, especially when it comes to the question of where these levels overlap. In this sense, a possible perspective is an evolutionary approach, which has great potential for unification with other sciences.